The perception of languages by Italian native speakers - NITTI, PAOLO; FACCHETTI, GIULIO (Glottodidactica, 2021)
This essay showcases the results of a survey conducted on a sample of Italian speakers which focused on their perception of languages. The research, carried out in the second half of 2019, has enabled corroborating the initial hypothesis about the existence of preconceptions and stereotypes associated with the perception of foreign languages and cultures (Elman & McClelland 1986) by Italian people. In particular, a questionnaire was used to clarify which adjectives are commonly associated with selected foreign languages, in order to identify certain trends and stereotypes. The survey is based on ethnolinguistic and language education studies (Cardona 2006), and was performed through data collection techniques used in ethnography and sociolinguistics (Tagliamonte 2006).